PUBLIC SERVICE STANDARDS IN THE CITY'S LABOR DEPARTMENT MAKASSAR CITY - Arhas, Sitti Hardiyanti; Niswaty, Risma; Suprianto, Suprianto; Jamaluddin, Jamaluddin (Natapraja, 2022)
Improving the quality of public services and people feeling satisfied with these services is the ultimate goal of bureaucratic reforms carried out by the government. The purpose of this study is to provide an in-depth overview of public services at the Makassar City Manpower Office. To answer the research objectives, a qualitative type of research with a descriptive approach is used. The data collection method used was an in-depth interview with 5 informants. 3 informants are employees of the Makassar City Manpower Office, while the other 2 are service recipients. To obtain maximum results, the data obtained are analyzed by the stages of data condensation, data presentation and drawing conclusions. Based on the results of the study that overall public services in the Makassar City Manpower Office are good, this is characterized by service requirements that are easy to be met by the community. Fairly clear systems, mechanisms and procedures. The quality of the products offered is in accordance with the main duties and functions of the Makassar City Manpower Office. The completion period is quite good but sometimes the service exceeds the predetermined SOP. The service fee is not there or free, the recipient of the service only charges the doubling money. The results of this study are useful as input for the Manpower Office to continue to make improvements in providing services to the community such as continuing to update the official homepage owned, so that the public is easy to access information without having to go to the Makassar City Manpower Office.